Penanaman Nilai-Nilai Keislaman Bagi Siswa di SMK Bina Mandiri Multimedia - Molbi Febrio Harsanto; Hernawan Hanif; Triyana; Rahmawati; Tresna Panca Desyana (Jurnal Pengabdian Masyarakat Madani, 2022)
Education is a learning process that is passed down from one generation to the next generation. Education that is side by side with the inculcation of Islamic values can shape the character of students who are akhlakul kharimah. Many of educational institutions that only provide knowledge transfer without any transfer of values has an impact on many of juvenile delinquencies that occur. Instilling Islamic values in adolescent students greatly influences the way students thinking, behave, and interaction in daily life. This service activity was carried out at the SMK Bina Mandiri Multimedia. The process of this activity is carried out by means of socialization and discussion. After participating in this activity, the students of SMK Bina Mandiri Multimedia better understand the need to instill Islamic values in the school environment and also apply them in daily life.